5-HT2C Receptors Localize to Dopamine and GABA Neurons in the Rat Mesoaccumbens Pathway - Bubar, Marcy J.; Stutz, Sonja J.; Cunningham, Kathryn A. (PLOS ONE, 2011)
The serotonin 5-HT2C receptor (5-HT2CR) is localized to the limbic-corticostriatal circuit, which plays an integral role in mediating attention, motivation, cognition, and reward processes. The 5-HT2CR is linked to modulation of mesoaccumbens dopamine neurotransmission via an activation of γ-aminobutyric acid (GABA) neurons in the ventral tegmental area (VTA). However, we recently demonstrated the expression of the 5-HT2CR within dopamine VTA neurons suggesting the possibility of a direct influence of the 5-HT2CR upon mesoaccumbens dopamine output. Here, we employed double-label fluorescence immunochemistry with the synthetic enzymes for dopamine (tyrosine hydroxylase; TH) and GABA (glutamic acid decarboxylase isoform 67; GAD-67) and retrograde tract tracing with FluoroGold (FG) to uncover whether dopamine and GABA VTA neurons that possess 5-HT2CR innervate the nucleus accumbens (NAc). The highest numbers of FG-labeled cells were detected in the middle versus rostral and caudal levels of the VTA, and included a subset of TH- and GAD-67 immunoreactive cells, of which >50% also contained 5-HT2CR immunoreactivity. Thus, we demonstrate for the first time that the 5-HT2CR colocalizes in DA and GABA VTA neurons which project to the NAc, describe in detail the distribution of NAc-projecting GABA VTA neurons, and identify the colocalization of TH and GAD-67 in the same NAc-projecting VTA neurons. These data suggest that the 5-HT2CR may exert direct influence upon both dopamine and GABA VTA output to the NAc. Further, the indication that a proportion of NAc-projecting VTA neurons synthesize and potentially release both dopamine and GABA adds intriguing complexity to the framework of the VTA and its postulated neuroanatomical roles.